(untitled) (Advances in Applied Mathematics and Mechanics, 2020)
This article is devoted to the development of a new approach for stress recovery in the isogeometric analysis method which makes use of equilibrium of patches. It is shown that the obtained stresses of this approach are more accurate than our previous work based on using the super convergent property of the Gauss quadrature points. To demonstrate the efficiency of this error estimator, a few examples of elasticity problems with available analytical solutions are ‎modeled and solved. The obtained results are ‎compared with the exact solutions as well as our ‎previous method. These ‎results indicate superiority of the current method that can be considered ‎as a simple and ‎efficient approach for stress recovery and error estimation in the isogeometric ‎analysis ‎method.